The Orao Affair: The Key to Military Integration in Post-Dayton Bosnia and Herzegovina. Issue 1 (2nd January 2018) - Short, Elliot
ABSTRACT: Following Dayton, three ethnocentric armies remained in Bosnia and Herzegovina, presenting a significant obstacle to the consolidation of the multi-ethnic Bosnian state. This article examines the development of the separate armies and the reform process that ultimately unified them. It will contend that such progress would not have been possible without the political fallout that followed the revelation that a Bosnian company had been conducting trade with Iraq in contravention of a UN embargo prior to the 2003 invasion. Faced with the threat of international sanctions, local and international actors moved rapidly to overhaul the defense sector, resulting in the military integration of the three armed forces and the creation of a single army answerable to the Bosnian state.